Pendampingan Pembelajaran Agama Islam Dengan Memanfaatkan Media Ajar Di TPA Al-Amien - Fajaruddin, Achmad; Fa'uni, Maayang; Almahbubah, Izzah (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Education is an inseparable fundamental right from learning. For the realization of good education, learning motivation and learning media are necessary. Education itself has many scopes, one of which is Islamic religious education. The learning of Islamic religion at TPA Al-Amin is hindered by the lack of learning media, which reduces the motivation of learners. This activity takes place in Kembang Village, Girimulyo, Ngawi, with 10 participants. The purpose of this mentoring activity is to enhance the quality of religious education and increase student motivation through the use of diverse teaching media. The methods used in this mentoring include observation, program development, practice, and evaluation. This community service activity is carried out in Girimulyo Village, Jogorogo, Ngawi, East Java. This study involves 34 students. The results of this study indicate a significant increase in learning motivation after the implementation of teaching media in learning at TPA Al-Amien.